A case of de Garengeot hernia: the feasibility of laparoscopic transabdominal preperitoneal hernia repair - Al-Subaie, Saud (Int J Surg Case Rep, 2015)
INTRODUCTION: de Garengeot hernia is described as the presence of an appendix in a femoral hernia. This rare hernia usually presents with both diagnostic and therapeutic dilemmas. PRESENTATION OF CASE: We report a case of a 59 year-old woman with a one-year history of a right irreducible femoral hernia. She underwent diagnostic laparoscopy with an intraoperative diagnosis of de Garengeot hernia. This was followed by a laparoscopic transabdominal preperitoneal (TAPP) approach for hernia repair. DISCUSSION: The long-standing presentation of de Garengeot hernia is seldomly reported in literature. There has been no standard approach of treatment for de Garengeot hernias described, possibly due to the rarity of this condition. The unusual presentation of the hernia prompted us to undergo a diagnostic laparoscopy first, during which the appendix was seen incarcerated in a femoral hernia sac. We were easily able to proceed for a laparoscopic TAPP approach for hernia repair without the need for conversion to an open repair. CONCLUSION: We were able to obtain an accurate diagnosis of an appendix within a long-standing irreducible femoral hernia through diagnostic laparoscopy followed by transabdominal preperitoneal (TAPP) approach for hernia repair. We would like to underline the usefulness of laparoscopy as a valuable tool in the diagnosis and treatment of this unusual presentation of groin hernias.